The Determinants Of Macroeconomic Factors On The Return Of Real Estate Investment Trusts In Malaysia - Muhammad Najib Razali, Rohaya Abdul Jalil, Thi Kim Nguyen (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is to examine the macroeconomic determinants on real estate investment trusts (REITs) return volatility in Malaysia. The sample period of this study is eight years from 2010 Q1 to 2017 Q4. In this study, the REIT return volatility and its macroeconomic determinants are examined. This study employed Autoregressive Conditional Heteroscedasticity (ARCH) and Generalised Autoregressive Conditional Heteroscedasticity (GARCH) models to assess the volatility for REIT returns. Furthermore, the analysis also aims to evaluate the significance of macroeconomic determinants on REIT return volatility in Malaysia. The findings revealed several macroeconomic factors such as Base Lending Rate (BLR), money supply, industrial production, Gross Domestic Product (GDP) and Consumer Price Index (CPI) were the major factors in determining the return of REITs in Malaysia. This study has an implication for investors and fund managers when they have to consider REIT return volatility in investment decision-strategic decision making. This research will also provide more information on the REIT investment risk levels as the property portfolio market has become more complex and requires more transparency in terms of information.